Development of geriatric syndromes after taking countermeasures for polypharmacy: an overlooked issue of quitting semiregular single-dose medicine. Issue 6 (14th June 2019) - Tomita, Naoki; Ishiki, Aiko; Okinaga, Shoji; Furukawa, Katsutoshi; Arai, Hiroyuki
ABSTRACT: We report a case of an elderly woman on polypharmacy who developed appetite loss, general fatigue and muscle weakness mainly from secondary adrenal insufficiency caused by quitting one semiregular single-dose medicine. Because the degree of insufficiency was mild, her symptoms were eliminated after some time without additional treatment. The present case includes important lessons related to medication management in elderly patients. Additionally, the present case also warns us to be cautious while diagnosing geriatric syndromes as a part of the physiological aging process or additional disease symptoms. Drug-induced geriatric syndrome from quitting semiregular-use drugs should be investigated in future studies.